Evaluasi Usability Aplikasi E-TPT Berbasis Mobile Kantor Pelayanan Pajak Pratama Malang Utara dengan Menggunakan Metode Heuristic Evaluation - Annisa Rahmadina; Ismiarta Aknuranda; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
e-TPT Kantor Pelayanan Pajak Pratama Malang Utara is an innovation application by Kantor Pelayanan Pajak Pratama Malang Utara. This application was made to support tax activity which is conducted by taxpayer. The main features of this application is to get queue number online. From the beginning of its publication, this application only focus on functionality and has not been tested for its usability. Therefore, heuristic evaluation is conducted to find out what usability problems exist in the application. The evaluators involved in this heuristic evaluation process were 3 evaluators. Usability evaluation using heuristic evaluation method resulted in a total of 30 problems. From these 30 usability problems, the average of severity ratings that is found can be classified into 3 of 4 category namely cosmetic, minor and mayor. The most usability problems are found in H-4 (Consistency and Standards) with total 7 problems or 23.3% from all problems found. While the highest average of severity rating is found in H-9 (Help User Recognize, Diagnose and Recovers User) which has an average severity ratings of 3. Improvement recommendations are made based on the results of the heuristic evaluation and produce 10 page designs and 6 pop-up / notification designs.